The Influence of Homeroom Teachers’ Role as Learning Coaches on Ninth-Grade Students’ Academic Grit - Tamrin Tamrin; Nasir Nasir; Titi Fatmawati (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to analyze the influence of the homeroom teacher’s role as a learning coach on the academic grit of ninth-grade students. In addition, this study examines the role of self-regulated learning as a mediating variable in the relationship between learning coaching and academic grit. The research employed a quantitative explanatory design complemented by qualitative analysis to deepen the interpretation of findings. Quantitative data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), while qualitative data were collected through interviews, observations, and documentation. The results indicate that the homeroom teacher’s role as a learning coach has a positive and significant effect on students’ self-regulated learning and academic grit. Self-regulated learning also shows a significant influence on academic grit and functions as a mediating variable. Qualitative findings support the quantitative results, revealing that reflective and personalized learning coaching practices enhance students’ learning autonomy, perseverance, and consistency in facing academic challenges. This study highlights the importance of optimizing the homeroom teacher’s role as a learning coach to strengthen academic grit and improve student support management in junior secondary schools.